Modern Payment Solutions for Zakat Fitrah: a Shariah Legal Examination of Pay Later Systems in Marketplaces - Saekhu, Saekhu; Musyafak, Najahan; Mahsun, Mahsun (Economica: Jurnal Ekonomi Islam, 2022)
This study examines the use of Pay Later systems offered by digital marketplaces, such as Gopay and Shopee, as a method for fulfilling zakat fitrah obligations. While financial technology has enhanced accessibility and efficiency in zakat management, its integration with credit-based instruments raises significant Shariah concerns. This study is contextualized from a qualitative approach that combines normative legal analysis with digital ethnography, exploring whether deferred payment models align with Islamic jurisprudence and the objectives of Shariah. We highlight findings that although Pay Later provides convenience for zakat payers, it introduces elements of debt that risk contradicting the principle of immediacy in zakat fitrah. Nonetheless, under certain circumstances, such as compliance with DSN-MUI regulations and avoidance of riba, Pay Later may be considered permissible as a means of fee. This paper contributes to the growing discourse on Islamic fintech by clarifying the legal and ethical boundaries of credit-based worship payments and offers practical recommendations for zakat institutions to collaborate with fintech providers while safeguarding the integrity of religious obligations.